A comprehensive study on the effects of alternative sulphur precursor on the material properties of chemical bath deposited CdS thin films - Azmi N.; Chelvanathan P.; Yusoff Y.; Shahahmadi S.A.; Tiong S.K.; Sopian K.; Amin N. (Elsevier Ltd, 2023)
Amorphous films; Cadmium sulfide; Carrier concentration; Deposition; Energy gap; II-VI semiconductors; Lime; Morphology; Substrates; Surface morphology; Surface roughness; Thioureas; Average surface roughness; Chemical-bath deposition; Granular structuress; Micro-structural; N-methylthiourea; Optical and electrical properties; Precursor concentration; Soda lime glass substrate; Thin films